PERFORMANCE REVIEW OF PROJECT’S STAFF OF IT COMPANIES - PETRENKO, Oleksandr; MAZORENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the main current theoretical and practical aspects of «Performance review» for assessing the projects of Ukrainian IT companies. Analysis, synthesis, system analysis, and alignment method are the main methods was determined in the course of scientific research. The basic stage is the identification of the main changes. until the launch of «Performance Review» for Ukrainian IT companies. become practical in Ukrainian IT companies and replace traditional methods of HR work. An important aspect of refining traditional evaluation systems is: correcting the imbalance between the goals of the company and the specific goals of employees; uniqueness of subjective evaluation; reaching the right level of those who evaluate; ensuring clear and uninterrupted communication with one-to-one connections; achieving rational results assessments to ensure proper motivation, forming directives for beginning and development, career growth, etc. The key element of the «Performance review» is the use of the «180 degrees», «360 degrees» and «extended 180 degrees» methods. The choice of the cutaneous method depends on specific minds in the IT company, which in turn outlines the main advantages of the cutaneous method. The main result of the investigation is the formation of a standard river calendar schedule for «Performance review» on projects of current IT companies. In the following, practical applications of forming goals using the SMART methodology are outlined. It is important to note that the Performance review includes an assessment of the achieved goals and the type of activities carried out in the planting process, as well as the possibility of moving to a higher grade. The implementation of a cyclical plan for evaluating employees aligns with their individual development and achievement of the company’s key goals.
Keywords: staff assessment; project; «Performance review»; «360 degrees method»; «180 degrees method»; goal setting; IT company; feedback